2019
DOI: 10.32663/edu-ling.v3i1.1315
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing EIL Using “Memrise” As A Builder Students’ Vocabularies

Abstract: Although the online English learning platform currently is interesting and entertaining and it can improve language acquisition, pronunciation, four integrated skills but it still becomes difficult to be used in English learning. Therefore, people must be mastering high technology to support their daily life and get much information instantly and accurately. In this article, the writer would like to introduce a suitable platform in English learning. English is considered as an international language (EIL) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…They also seemed to be more enjoy and comfortable when learning English using the application. Moreover, Melati & Herlina (2019) also found out that the wide variety of features in similar application such as Hello English can make the students more interested in learning English especially vocabulary which is advantageous in improving the students' perception.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They also seemed to be more enjoy and comfortable when learning English using the application. Moreover, Melati & Herlina (2019) also found out that the wide variety of features in similar application such as Hello English can make the students more interested in learning English especially vocabulary which is advantageous in improving the students' perception.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have confirmed that the impact of Mobile Application such as Hello English Application has improved students' vocabulary, such as Fathi et al, (2018); Izah, (2019); Melati & Herlina, (2019), These studies discovered that the implementation of Mobile Application such as Hello English could improve the students' vocabulary mastery. It can be considered as appropriate learning tools for students (Bensalem, 2018;Çelik, 2017;Okumus Dagdeler et al, 2020;Shahbaz & Khan, 2021;Yuan, 2019).…”
Section: Hello English Applicationmentioning
confidence: 92%
See 1 more Smart Citation
“…Keunggulan Memrise terletak pada strategi pembelajarannya yang mendukung, menyenangkan, mudah dipahami, dapat diakses secara intensif dan fleksibel dengan m-learning, serta melatih kemahiran mendengar, membaca dan menulis dengan baik, sementara kelemahannya adalah Memrise masih berbasis daring (Fajrina et al, 2017). Innovation in learning is supported by learning strategies and the application of media in learning avtivity such MEMRiSE is very significant to create effective and creative English language learning, especially the current situation of COVID-19 pandemic (Melati & Herlina, 2019). Memrise is an application which can be found in an android has improved the student's mastery of irregular verbs (Rosydah, 2018); (W. H. Setyawan & Nawangsari, 2021).…”
Section: Pendahuluanmentioning
confidence: 99%
“…Memrise has been widely used as a powerful tool in helping learners learn English vocabulary worldwide (Melati and Herlina, 2019). However, only a few studies on the use of Memrise have been conducted in the context of Vietnam, where English language teaching has been said to be different from other contexts due to its policies and also the influence of traditional form-based teaching methods (Nguyen and Jaspaert, 2021).…”
Section: Introductionmentioning
confidence: 99%